Method for quantifying oxidized methionines and application to HIV-1 Env - Shipman, Joshua T. (J Am Soc Mass Spectrom, 2018)
Recombinantly expressed proteins are susceptible to oxidation during expression, purification, storage and analysis; the residue most susceptible to oxidation is methionine. Methionine oxidation can be overestimated using current quantitative analysis methods because oxidation can occur during sample preparation, and researchers often do not use methods that account for this possibility. An experimental strategy had been developed previously to solve this problem through the use of an (18)O labeled hydrogen peroxide reagent. However, the method did not address the analysis of peptides that contained multiple methionine residues. Herein, we develop and validate a new analysis method that uses theoretical isotope distributions and experimental spectra to quantify methionine oxidation that is present prior to sample preparation. The newly described approach is more rapid than the previously described method, and it needs only half the amount of protein for analysis. This method was validated using model proteins; then it was applied to the analysis of recombinant HIV-1 Env, the key protein in HIV vaccine candidates. While Met oxidation of this protein could not be analyzed using previous methods, the approach described herein was useful for determining the oxidation state of HIV-Env.